Honorários advocatícios na fase de cumprimento de sentença das obrigações ao pagamento de quantia certa, de acordo com a Lei nº. 11.232/2005 - Nascimento, Rubiane Silva (2014)
This thesis aims to identify the best approach as to whether or not attorney fees should be charged during compliance of judgment phase. The law n. 11.232/2005 has eliminated the enforcement process related to the obligation to pay certain amounts, transforming in procedural stage. Following this change in legislation, a lot of controversies arose. However, in order to conclude the applicability of attorney fees, this thesis describes the evolving of civil procedure since the first civil Procedural Code as of 1939 until the present, focusing on the main procedural reforms taken place in the last years. It also briefly describes principles of executive tutelage and to dig deeply into the subject under discussion, it will be necessary to briefly assess this new procedural phase. At last, all the approaches to this discussion will be presented as well as a few other considerations. Because this is a very controversial topic - with many conflicting precedents being made over the years - it deserves to be properly analysed